2018
DOI: 10.1111/jan.13527
|View full text |Cite
|
Sign up to set email alerts
|

Fathers’ experiences with their preterm babies admitted to neonatal intensive care unit: A multi‐method study

Abstract: Fathers of preterm infants should receive personalized support specifically addressed to them and based on the infant's gestational age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 53 publications
4
66
0
Order By: Relevance
“…There is sufficient scientific evidence to support the application of somatic stimulation in preterm infants during hospitalization (Diego et al, 2007;Fallah et al, 2013;Guzzetta et al, 2009;Jabraeile et al, 2016;Massaro et al, 2009), owing to its benefits on multiple aspects associated with prematurity: Increase in weight and size (Diego et al, 2007;Field et al, 2008;Jabraeile et al, 2016;Kumar et al, 2013;Massaro et al, 2009;Niemi, 2017) and facilitation of psychomotor development and brain maturation (Fucile & Gisel, 2010;Guzzetta el al., 2011;Ho et al, 2010;Lai et al, 2016;Procianoy, Mendes, & Silveira, 2010;Stefana et al, 2018) However, there are many hospitals that have not incorporated somatic stimulation in the care given to preterm infants.…”
Section: Discussionmentioning
confidence: 99%
“…There is sufficient scientific evidence to support the application of somatic stimulation in preterm infants during hospitalization (Diego et al, 2007;Fallah et al, 2013;Guzzetta et al, 2009;Jabraeile et al, 2016;Massaro et al, 2009), owing to its benefits on multiple aspects associated with prematurity: Increase in weight and size (Diego et al, 2007;Field et al, 2008;Jabraeile et al, 2016;Kumar et al, 2013;Massaro et al, 2009;Niemi, 2017) and facilitation of psychomotor development and brain maturation (Fucile & Gisel, 2010;Guzzetta el al., 2011;Ho et al, 2010;Lai et al, 2016;Procianoy, Mendes, & Silveira, 2010;Stefana et al, 2018) However, there are many hospitals that have not incorporated somatic stimulation in the care given to preterm infants.…”
Section: Discussionmentioning
confidence: 99%
“… Family-Integrated Care (FIC) (Lee & O'Brien, 2018)  Parent involvement / participation in care (Ottosson & Lantz, 2017)  Include the whole family; fathers (Stefana et al, 2018), siblings (Morrison & Gullon-Rivera, 2017) and grandparents in care and visitation policies.  Educate parents and empower them to be "experts"…”
Section: Examples Of Strategiesmentioning
confidence: 99%
“…In addition, soon after the birth, men will generally be the fi rst to enter the NICU and establish contact with the baby (Arnold et al, 2013). Some authors have shown that fathers are immediately involved with the baby, especially when they are encouraged by the team to approach the baby and have opportunities for physical contact (Fegran, Helseth, & Fagermoen, 2008;Stefana, Padovani, Biban, & Lavelli, 2018). Whereas other studies have highlighted that fathers may feel frightened by the NICU technology, imagining that by touching the baby, they may interfere with the baby's care and/or may cause an infection (Arnold et al, 2013;Hollywood & Hollywood, 2011;Stefana et al, 2018).…”
mentioning
confidence: 99%
“…Some authors have shown that fathers are immediately involved with the baby, especially when they are encouraged by the team to approach the baby and have opportunities for physical contact (Fegran, Helseth, & Fagermoen, 2008;Stefana, Padovani, Biban, & Lavelli, 2018). Whereas other studies have highlighted that fathers may feel frightened by the NICU technology, imagining that by touching the baby, they may interfere with the baby's care and/or may cause an infection (Arnold et al, 2013;Hollywood & Hollywood, 2011;Stefana et al, 2018). The possibility of touching the baby can generate contrasting feelings, from excitement and joy to fear of causing harm to the baby and disappointment that they do not have permission to touch their child.…”
mentioning
confidence: 99%
See 1 more Smart Citation